Microneedles for Proteins and Peptides Delivery: Current Aspect and Future Perspective - Pattewar, Renuka (Asian Journal of Pharmaceutics (AJP), 2024)
More than half of the top 20 most famous drugs fall under biopharmaceuticals, with projections indicating a $388 billion value by 2024 that shows how effective protein, peptide, and antibody-based treatments are. However, the methods for effective medication delivery have been limited by the inherent characteristics of biopharmaceuticals. Although the intravenous route offers 100% bioavailability, patients frequently link it with discomfort and needle anxiety, which might result in resistance to receiving necessary therapy. Since then, several non-invasive techniques have been developed to get beyond these restrictions. One such tactic is microneedles (MNs), which can painlessly pierce the stratum corneum barrier and significantly improve transdermal medication delivery of various medicines. This review summarizes several studies that strive to enhance MN-based transdermal biopharmaceutical delivery. The ability to increase MN production at a lower cost and the application’s long-term safety will be key factors in determining the full potential of MNs as a drug delivery technology for biopharmaceuticals. Thus, the existing obstacles to the clinical translation of MNs are also examined, along with potential solutions.